Effect of pumice stone and pearlite abrasives characteristics on denim abrasion. (June 2022) - Elaissi, Arwa; Alibi, Hamza; Ghith, Adel
The manufacture of abrasives based on waste grains of pumice stones and pearlites represents the aim of this work is to minimize both the cost of the product and to recover industrial waste that harms the environment. We also used a non-woven based on cellulosic fibers as reinforcement and three types of resins (polyurethane, acrylic, and polyester). Obtaining these products is designed by two processes (by spraying and by coating). The effect of the manufacturing process, the type and size of the grains on the abrasive wear of denim fabrics, the material removal rate (MRR), and the surface morphologies obtained were quantitatively evaluated. A chemical analysis (FTIR) and a thermal analysis were carried out (ATG/DSC). Scanning electron microscopy (SEM) was performed to see the appearance of these grains and measure their diameter. Inductively Coupled Plasma Mass Spectrometry (ICP/MS) analyses show that pumice grains contain more calcium atoms than pearlite grains. The different abrasion grains were compared according to their polishing effect. We note that the abrasive manufacturing process, type, and size of abrasive particles affect the MRR. Pumice grits allow for deeper polishing compared to other grits.